An Analysis of Billy Joel’s Song Lyric Vienna Using Psychoanalytic Literary Criticism Theory - Vanesa Liu; Putu Lirishati Soethama; Ida Ayu Made Puspani; Ni Ketut Alit Ida Setianingsih (Jurnal Langua, 2023)
Psychoanalytic criticism employs Freud's and following theorists' "reading" techniques to interpret texts. It is argued that literary texts, like dreams, reveal the author's unconscious desires and worries; a literary work is an expression of the author's neuroses. It is possible to psychoanalyze a specific literary character, however it is generally accepted that all such characters are reflections of the author's personality. A remarkable characteristic of this method is that it affirms the significance of literature by utilizing a literary key for decoding. Freud himself penned, "The dream-thoughts that we first encounter in the course of our analysis often blow us by the unusual form in which they are expressed; they are not clothed in the prosaic language typically employed by our thoughts, but are instead represented symbolically through similes and metaphors, in images resembling poetic speech". This analytical attempt, like psychoanalysis itself, seeks evidence of unresolved emotions, psychological conflicts, guilts, ambivalences, etc. within a potentially disjointed literary work. The author's personal childhood traumas, family life, sexual difficulties, and fixations will be reflected in the conduct of the literary work's characters. Yet psychological material will be expressed indirectly, disguised, or encoded (as in dreams) via concepts such as "symbolism" (the repressed object represented in disguise), "condensation" (many thoughts or individuals depicted in a single image), and "displacement" (anxiety located onto another image by means of association). Many artists expressed their thoughts, anxiety, and buried dreams through song lyrics. One of which is Billy Joel with his song Vienna. The qualitative research method was used to analyze the data in this study. The lyrics of Vienna’s song are analyzed utilizing psychoanalytic literary criticism theory as the guidelines. The findings show that this song contains many elements of psychoanalytic through the metaphors that Billy Joel used in the lyrics.